Symeon the Holy fool: Leontius's life and the late antique city - Krueger, Derek; Leontius Neapolitanus 600-670 (The transformation of the classical heritage, 1996)
Of the hagiographical writings which survive from Late Antiquity, perhaps none has more potential to amuse and scandalize the reader, ancient or modern, than the Life and Conduct of Abba Symeon Called the Fool for the Sake of Christ, written by Leontius, the bishop of Neapolis on Cyprus (modern Limassol) near the middle of the seventh century. Pretending to be insane, Symeon the monk walks about naked, eats enormous quantities of beans, and defecates in the streets. Although Leontius was not the first to relate a tale of a Christian saint who pretended to be crazy, the Life of Symeon is the first full-length vita of a holy fool.